Integrating Equity and Reconciliation Work into Archival Descriptive Practice at the University of Waterloo - Robichaud, Danielle (Archivaria, 2021)
Despite sustained calls for a critical review of harmful content within archival descriptive records, there remains much to be explored by way of implications for Canadian academic archives. This article addresses the absence of Canadian archival practitioners in broader discussions about the revision and remediation of descriptive records by exploring how staff in Special Collections & Archives at the University of Waterloo Library are working to integrate equityand reconciliation-informed thinking into the department’s archival practice by revising their approach to language in archival descriptions. Beginning with an overview of the department and the landscape in which it operates, this article provides a brief review of guidance available in the Rules for Archival Description. It then provides the rationale behind the recent changes to descriptive practice before exploring a series of examples of how and where this work is newly underway. The article concludes with a consideration of current identified challenges and the related work ahead.